Bone turnover markers and the factors associated with atypical femur fractures among Japanese patients. Issue 11 (November 2016) - Iizuka, Yoichi; Iizuka, Haku; Kaneko, Tetsuya; Mieda, Tokue; Takechi, Rumi; Suzuki, Hideki; Sorimachi, Yasunori; Suto, Takahito; Tachibana, Masahiro; Yoneyama, Tomotaka; Omodaka, Takuya; Hashimoto, Shogo; et al.
Abstract: Many previous reports have indicated that atypical femur fractures (AFFs) are associated with the administration of bisphosphonates (BPs). A number of risk factors and hypotheses regarding the pathogenesis of AFFs have been reported to date. The purpose of the present study was to identify the factors associated with AFFs in Japanese individuals and to elucidate the association between bone metabolism and AFFs by evaluating bone turnover markers (BTMs). We prospectively reviewed all patients with femur fractures and identified the patients with AFFs and typical femur fractures (TFFs). We collected the demographic and clinical data that were relevant to the present study, namely age, gender, affected side, affected site, concomitant medical history, and comorbid conditions, and measured the levels of BTMs within 24 h after trauma. Welch's test and Fisher's exact probability test were used for the statistical analyses. A total of 338 patients, including 10 patients with AFFs and 328 patients with TFFs, were analyzed under the inclusion criteria. The use of BPs (p < 0.001) and collagen disease and chronic granulomatous disease (CD/CGD) (p = 0.025) were more frequently observed in patients with AFFs than in patients with TFFs, while the levels of BTMs, including N-terminal propeptides of type 1 procollagen (P1NP), isoform 5b of tartrate-resistant acid phosphatase (TRACP-5b) and undercarboxylated osteocalcin (ucOC) were significantly lower in patients with AFFs than in patients with TFFs. Furthermore, the level of TRACP-5b was found to be significantly lower in patients with atypical subtrochanteric fractures than in atypical diaphyseal fractures (p = 0.025). Moreover, the levels of P1NP (p = 0.016) and TRACP-5b (p = 0.015) were found to be significantly lower in patients with AFFs than in patients with TFFs in a subgroup analysis of BPs users. The use of BPs was considered to be a factor associated with AFFs. Our comparison of the BTMs in patients with AFFs and TFFs indicated that the severe suppression of bone turnover was associated with the pathogenesis of AFFs. The extent of the influence of suppressed turnover on the pathogenesis of AFFs may differ depending on the fracture site.